2000
DOI: 10.1074/jbc.275.16.12175
|View full text |Cite
|
Sign up to set email alerts
|

Lead and Calcium Produce Rod Photoreceptor Cell Apoptosis by Opening the Mitochondrial Permeability Transition Pore

Abstract: Calcium overload is suggested to play a fundamental role in the process of rod apoptosis in chemical-induced and inherited retinal degenerations. However, this hypothesis has not been tested directly. We developed an in vitro model utilizing isolated rat retinas to determine the mechanisms underlying Ca Apoptosis is an active mode of cell death that is induced by a variety of physiological and pathological stimuli. Convergent evidence suggests that mitochondria and caspases play a central and fundamental role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
154
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(163 citation statements)
references
References 58 publications
9
154
0
Order By: Relevance
“…4), Ca 2+ was not added, but, by operating under conditions similar to those reported in the literature [19,20] (i.e., 0.25 M sucrose, 10 mM Hepes/Mops pH 7.4, 5 lM CaCl 2 ), the addition of small amounts of Co 2+ (around 10 lM) induces a swelling, and the swelling is cyclosporine-sensitive (not shown). The above mentioned evidence appears to indicate similar targets for Co 2+ , Zn 2+ , and Pb 2+ , but in the cases of Zn 2+ and Pb 2+ [19,20] the authors have not proposed a specific action site for these two metals.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…4), Ca 2+ was not added, but, by operating under conditions similar to those reported in the literature [19,20] (i.e., 0.25 M sucrose, 10 mM Hepes/Mops pH 7.4, 5 lM CaCl 2 ), the addition of small amounts of Co 2+ (around 10 lM) induces a swelling, and the swelling is cyclosporine-sensitive (not shown). The above mentioned evidence appears to indicate similar targets for Co 2+ , Zn 2+ , and Pb 2+ , but in the cases of Zn 2+ and Pb 2+ [19,20] the authors have not proposed a specific action site for these two metals.…”
Section: Discussionmentioning
confidence: 89%
“…With regard to Zn 2+ [19] and Pb 2+ [20], the opening of the MTP pore has been observed in the presence of micromolar amounts of Ca 2+ . In our experiments (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, TRAIL-induced caspase-3 activation is su cient to cause apoptosis without the involvement of mitochondria, as cyclosporin A (CsA) delays, but does not block, caspase-3 activation and apoptosis. In other systems where apoptosis occurs via mitochondrial-dependent pathway, CsA blocks caspase-3 activation and apoptosis (Susin et al, 1998;He et al, 2000). It is not known whether TRAIL induces early response gene.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, accelerated Na ϩ /Ca 2ϩ influx would drive the intracellular [Ca 2ϩ ] to higher than normal levels until they are sufficient to inactivate the mutant cyclase. Previous studies have suggested that elevated [Ca 2ϩ ] plays a fundamental role in the process of apoptotic rod cell death in humans and animals during inherited retinal degenerations, retinal diseases, injuries, and chemical exposure (67).…”
Section: Discussionmentioning
confidence: 99%